Social Ties in Online Networking - Ivana, Greti-Iulia (Palgrave Studies in Relational Sociology, 2018)
This book explores the relevance of social networking from the perspective of its users to reveal the sociological significance of (inter)active experiences on Facebook. In doing so, the work examines obscure aspects of Facebook by addressing such questions as: What constitutes keeping in touch?; how is knowing of the other different from being with the other?; and why is the presence of others such an important element of Facebook? Social Ties in Online Networking discusses the significance of social networking activity through a collection of interviews with the users of Facebook. It analyses what they do, what they like and watch, but first and foremost how they intend their own actions and others' actions to be perceived within the realm of social media. This book is an exploration of relationships, which will be of interest to academics and students in sociology, social theory, human geography, social networking, media studies and social psychology.